Can Your Leadership Increase Mine? Enabling IT Self-Leadership Through Transformational IT Leadership - Eseryel, U. Yeliz (Journal of Leadership, Accountability and Ethics, 2024)
Despite substantial investments by companies in technology projects, these resources are often not utilized to their maximum capability. People can enhance their use of technology by taking leadership in their IT use, i.e., by exhibiting IT self-leadership. This way, they may contribute to applying technology in ways that boost the innovativeness of their team. Therefore, the more IT self-leadership employees exhibit, the better the IT-utilization of the organization is. This study investigates the connection between the team leaders’ transformational IT leadership and team members’ IT self-leadership. Findings from diverse European teams in various industries indicate a positive relationship between the two.